Texts, Identities, and Ethics: Critical Literacy in a Post‐Truth World. Issue 1 (25th June 2018) - Janks, Hilary
Abstract: This department explores critical perspectives on issues at the intersection of policy and practice in order to generate fresh questions about enduring dilemmas, new challenges, and debates.